2015
DOI: 10.4172/2155-9821.1000197
|View full text |Cite
|
Sign up to set email alerts
|

Beta-Glucosidase: Key Enzyme in Determining Efficiency of Cellulase and Biomass Hydrolysis

Abstract: Overall economics of the biomass to ethanol process is largely determined by the efficiency of biomass hydrolysis. Performance of cellulase cocktails used for saccharification of cellulose in biomass is often limited by lower amounts of β-glucosidases present, which catalyse hydrolysis of cellobiose, the product of endo and exocellulases to glucose. Inappropriate ratio of these enzymes in commercial cocktails leads to accumulation of cellobiose which inhibits the activity of cellulases. Thus, this rate limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 93 publications
(96 reference statements)
0
16
0
2
Order By: Relevance
“…Nevertheless, because of the insufficient presence of β-glucosidase (BGL) in T. reesei, cellulase preparations improvement should be carried out for cost-effective saccharification (Escamilla-Alvarado et al 2016). The supplementation and enhancement of BGL produced by other microbes in cellulase preparations is a promising method (Vijaya Rani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, because of the insufficient presence of β-glucosidase (BGL) in T. reesei, cellulase preparations improvement should be carried out for cost-effective saccharification (Escamilla-Alvarado et al 2016). The supplementation and enhancement of BGL produced by other microbes in cellulase preparations is a promising method (Vijaya Rani et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature for enzyme activity was found to be 50°C and pH 6.0-6.5. Activity parameters from many fungi and yeasts have been summarised (Rani et al, 2015), where temperature optima was found to mostly lie between 30-60°C while pH optima lie in the range of 4.0-6.5 while certain β-glucosidases from thermophiles, show higher temperature optima (Teugjas and Valjamae, 2013). While higher temperature optima increase catalytic efficiency but for selecting β-glucosidase, its compatibility with process set up is more important consideration.…”
Section: Discussionmentioning
confidence: 98%
“…Both the plant tissue composition and hydrolytic degradation of A. americana are evaluated in this study and compared to three advanced biofuel feedstocks that use the C 4 photosynthetic pathway (i.e., miscanthus, switchgrass, and sorghum). Previous work to increase fermentable products from lignocellulosic biomass includes improving pretreatment methods to increase enzymatic hydrolysis (Faik, 2013;Camesasca et al, 2015;Jin et al, 2016), biochemical engineering to improve enzyme activity (Zhang et al, 2006;Raghuwanshi et al, 2014), discovering novel cellulolytic enzymes (Zhang et al, 2006;Rani et al, 2014), optimizing enzyme blends for specific feedstocks (Gao et al, 2010), and decreasing the cost of enzymes (Klein-Marcuschamer et al, 2012;Culbertson et al, 2013;Johnson, 2016). This study specifically evaluated acid hydrolysis, enzymatic hydrolysis with a commercially available enzyme mixture, and saccharification of plant tissue from each of the four feedstocks to quantify the difference in conversion efficiency with difference tissue compositions.…”
Section: Introductionmentioning
confidence: 99%